Community Social Interaction on The Miai Riverbank - Thesya Noor Apriani; Bambang Subiyakto; Mutiani Mutiani; M. Ridha Ilhami; Muhammad Adhitya Hidayat Putra (The Innovation of Social Studies Journal, 2023)
The life of the people who live on the banks of the river is very focused on the river before the construction of the road. Over time the use of the river has changed, especially in people's lives. The community's social activities in Sungai Miai Village cover three aspects: interpersonal social interaction, the interaction between individuals and groups, and group-to-group social interaction. This study aims to describe the social activities of riverbank communities and the impact of social activities on rivers in Sungai Miai Village. This study uses a qualitative approach using descriptive methods. Data were obtained by triangulation of time, sources, and techniques presented in narration and pictures. The results showed that social activities in Sungai Miai Village included personal social interactions with individuals, individual social interactions with groups, and group social interactions. Some of the community's social activities still impact the existence of the river because some social activities still use the river for their daily life, although not all of their activities have implications for the river.